Grouped risk parity portfolios for stocks from the WSE - Gluzicka, Agata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The risk parity portfolios are characterized by equally weighted contributions of all assets. Very often, the idea of risk parity is considered as a special type of the diversification strategy. This approach became very popular among investors after the last economic crisis, when many portfolios perceived as well-diversified suddenly became undiversified portfolios. Usually, risk parity is calculated for individual stocks. In this article, the method of estimating risk parity portfolios for grouped stocks is discussed. The presented model is applied to selected stocks belonging to different groups (sectors, size of companies) and quoted on the Warsaw Stock Exchange. The main goal of the empirical research is the analysis of the risk parity portfolios calculated for the groups of stocks and also for individual stocks. Additionally, the risk parity portfolios are compared with the naive portfolios and minimum variance portfolios. All portfolios are compared according to the risk, rate of return, Sharpe ratio and the future profits
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 36-46
Keywords: risk parity portfolio; grouped risk parity; equally risk contribution portfolio; diversification; well-diversified portfolio; portfele parytetu ryzyka; grupowy parytet ryzyka; portfele o równymudziale ryzyka; dywersyfikacja; portfel dobrze zdywersyfikowany